Collocations in Letters to the Editor of Die Zeit - Skog-Södersved, Mariann; Malmqvist, Anita (Kalbotyra, 2020)
In the field of phraseology collocations have been less extensively researched than idioms. Because of their lower degree of idiomaticity collocations do not normally cause receptive problems in foreign language learning but need to be paid attention to when producing texts. We therefore argue that collocations are an important part of phraseology.The purpose of this paper is to investigate the syntactic structure, use and functions of collocations in 243 Letters to the Editor published in the German weekly newspaper Die Zeit. After consulting two dictionaries of collocations and some more universal sources a total of 278 collocations were identified and their respective bases and collocates were determined. The results show that nouns make up the majority of the bases (97%), while adjectives and verbs prevail among the collocates (96%). This is contradictory to the distribution of parts of speech in one of the two most comprehensive German dictionaries of collocations. A closer analysis of the empirical material reveals that the bases seem to reflect the subjects discussed in the letters, whereas the collocates provide the means for expressing the authors’ attitudes and values.
Keywords: phraseology; letter to the editor; basis; collocate; contents; values